Managing Digitalization in Finance via Robotic Process Automation - Nina GOGOLL (Communications of International Proceedings, 2021)
Data has reached the status of resources which are beneficial for effective steering of operative business and data provides possible increasing competitive advantages. The permanent increasing growth of workable structured and unstructured data volume plus the complexity of data-integration are issues which corporates are suspended with. Robotics Process Automation (RPA) is an instrument that has come into finance practice since the recent past. Out of the exponential rise of data and its necessary handling which jeopardizes the work capacity, the research motivation has evolve from the practical needfulness in finance practice. In order meet that request this paper follows the methodology of the formal-analytical research strategy with the simple and more or less abstract describing of problem structures (cp. Grochla, 1978, p. 85) by introducing the problem of the rising data flow. This is complemented partially by the factual-analytical research strategy wherein thorough investigation of complex interrelationships and hence a development of bases for actions (cp. Grochla, 1978, p. 72) whereby by presenting the practical business case of RPA in finance is reviewed based on secondary research method in order to receive an impression, if RPA is an useful instrument. The results are that a direct comparison between automated and manual execution disclose an annual return of approximately 30 percent with an amortization of circa three years and even up to an annual return would be 200 percent with six months amortization by production extension. Human actions are still need even though the roles of accounting and controlling will change.
Keywords: Finance; Robotics Process Automation; RPA